From eye to heart exterior spaces explored and explained - Burley, Jon; Machemer, Patricia ([United States] Cognella Academic Publishing, 2016)
"From eye to heart: exterior spaces explored and explained blends science, art, theory, and history to survey environmental design across significant cultures and places. Based on extensively class-tested material and the joint experiences of the authors as planners, designers, artists, and scientists, From Eye to Heart has a global perspective on the spaces humans create"-- Provided by publisher.
What is good enrvironment by Dr. Jon Bryan Burley, FASLA, Dr. Trisha Machemer, and Dr. C. Q. Liu -- China by Dr. Jon Bryan Burley, FASLA, Dr. Songlin Wei, Dr. C. Q.Liu, Dr. Xiaoying Li, A.S. Darkovskaya, Dr. Hui Wang, Si Chen, Yiwen Xu, and Dr. Trisha Macheimer -- Prehistory, Mesopotamia, and Egyptian landscape by Dr. Jon Bryan Burley, FASLA, Dr. Trisha Machemer, Paul Burley, and Shawn Partin -- Persia, Greece, and Anatolia by Dr. Jon Bryan Burley, FASLA, and Dr. Trisha Machemer -- Roman and Medieval environments by Dr. Jon Bryan Burley. FASLA, and Dr. Trisha Machemer -- India and Southeast Asia by Dr. Trisha Machemer and Dr. Jon Bryan Burley, FASLA -- Japan by Dr. Trisha Machemer and Dr. Jon Bryan Burley, FASLA -- Renaissance Italy by Dr. Jon Bryan Burley, FASLA, Dr. Trisha Machemer, and Eric Kopinsky -- Renaissance France by Julie Casault, Dr. Jon Bryan Burley, FASLA, and Dr. Trisha Machemer -- Renaissance England byJeremy Monsma, Dr. Jon Bryan Burley, and Dr. Trisha Machemer -- Portugal and Spain by Dr. Jon Bryan Burley, N.I.A, A.B. Rahman, F. Mo C. Mueller, E. Stanley, and Dr. Trisha Machemer -- Land planning European parks by Dr. Jon Bryan Burley, Eric Kopinsky, and Dr. Trisha Machemer -- Pre-columbian and American colonial environmental design: modern precedents to ancient traditions by Dr. Jon Bryan Burley, FASLA, and Dr. Trisha Machemer -- Contemporary design around the globe by Dr. Jon Bryan Burley and Dr. Trisha Machemer -- Landscape art by Dr. Jon Bryan Burley, Vincent Bouvier, Muriel Bouvier, and Dr. Trisha Machemer -- Art and environmental theory by Andrea Vanderwoude, Xiaowen Jin, Dr. Jon Bryan Burley, FASLA, Dr. Trisha Machemer, Sasha Darkovskaya, and Luis Loures -- Environmental research by Dr. Jon Bryan Burley, FASLA, and Dr. Trisha Machemer, Hui Wang, Sasha Darkovskaya and Luis Loures
Includes bibliographical references (pages 569-579) and index.
Keywords: Landscape design -- Textbooks; Landscape architecture -- Textbooks; Landscape drawing -- Textbooks; Human ecology -- Textbooks